Highly-sensitive H2S sensors based on flame-made V-substituted SnO2sensing films - J. Sukunta (2018)
© 2016 Elsevier B.V. In the present work, 0–2 wt% vanadium (V)-doped SnO2nanoparticles synthesized by flame spray pyrolysis were systematically studied for H2S detection. The sensing films (∼15–20 μm in thickness) were homogeneously prepared by spin coating technique on Au/Al2O3substrates. Structural characterizations by electron microscopy and X-ray analysis confirmed the formation of agglomerated SnO2nanoparticles (5–20 nm) with highly crystalline tetragonal-cassiterite SnO2structure and V substitutional doping with mainly V5+oxidation state. The gas-sensing studies revealed that the H2S response of flame-made SnO2nanoparticles was significantly enhanced by V doping at a very low concentration of 0.1 wt% but the response steadily degraded as the V-doping level increases further up to 2 wt%. In particular, the 0.1 wt% V-doped SnO2sensor exhibited a very high response of 2274 with a short response time of 2.0 s to 10 ppm of H2S at 350 °C. Moreover, the V-doped SnO2sensor displayed high H2S selectivity against NO, NO2, SO2, H2, C2H5OH and CH4. Hence, the flame-made V-doped SnO2sensor is a promising candidate for highly sensitive and selective of H2S monitoring and may be useful for general industrial applications.